Super-resolution microscopy: methods and protocols - Erfle, Holger (Methods in molecular biology, 2017)
Super-Resolution Microscopy Techniques and their Potential for Applications in Radiation Biophysics -- Managing the Introduction of Super-Resolution Microscopy into a Core Facility -- Live-Cell STED Imaging with the HyPer2 Biosensor -- Diffraction-Unlimited Fluorescence Imaging with an EasySTED Retrofitted Confocal Microscope -- Two-Photon STED Microscopy for Nanoscale Imaging of Neural Morphology In Vivo -- STED Imaging of Golgi Dynamics with Cer-SiR: A Two-Component, Photostable, High-Density Lipid Probe for Live Cells -- Four Channel Super-Resolution Imaging by 3-D Structured Illumination -- Correlative SIM-STORM Microscopy -- Correlative Super-Resolution Fluorescence Imaging and Atomic Force Microscopy for the Characterization of Biological Samples -- Quantitative Single-Molecule Localization Microscopy (qSMLM) of Membrane Proteins Based on Kinetic Analysis of Fluorophore Blinking Cycles -- Two-Color Single-Molecule Tracking in Live Cells -- Fully Automated Targeted Confocal and Single Molecule Localization Microscopy -- Brain Slice Staining and Preparation for Three-Dimensional Super-Resolution Microscopy -- Correlative In-Resin Super-Resolution Fluorescence and Electron Microscopy of Cultured Cells -- Synthesis of Janelia Fluor HaloTag and SNAP-Tag Ligands and their use in Cellular Imaging Experiments -- Measuring Nanometer Distances between Fluorescent Labels Step-by-Step -- Correlative Single Molecule Localization Microscopy and Confocal Microscopy -- Correlative Fluorescence Super-Resolution Localization Microscopy and Platinum Replica EM on Unroofed Cells -- In Situ Super-Resolution Imaging of Genomic DNA with OligoSTORM and OligoDNA-PAINT -- Super-Resolution High Content Screening and Analysis.